Effect of saline environment on the fatigue crack growth resistance of WE43 Mg alloy - Pereira, Gualter Silva (2022)
New magnesium alloys have been developed to reduce the weight of engineering components without compromising the mechanical properties and corrosion resistance; however, there is a lack in the literature regarding such properties. Hence, this work focuses on studying the fatigue crack propagation of the WE43 magnesium alloy, considering the effects of air and sodium chloride environments. Fatigue results showed similar behavior for both, main and transverse, directions regarding the rolling mill process. Yet, fatigue crack rates (FCR) were higher in the sodium chloride environment than in laboratory air, which could be attributed to hydrogen embrittlement and anodic dissolution at the crack tip. Laboratory air FCR results presented a lower m value (3.63 and 1.72) than the one found for the sodium chloride environment (9.15 and 4.83), indicating a lower FCR rate variation with ΔK. Comparing FCR for saline and air conditions, at the end of Paris' region II, FCR in the saline environment was enhanced by almost two orders of magnitude (ΔK= 11 MPa.m1/2). Furthermore, fractography showed mixed intergranular and transgranular cracking in the saline environment.